2014
DOI: 10.1007/s12374-014-0902-7
|View full text |Cite
|
Sign up to set email alerts
|

Master regulators in plant glucose signaling networks

Abstract: The daily life of photosynthetic plants revolves around sugar production, transport, storage and utilization, and the complex sugar metabolic and signaling networks integrate internal regulators and environmental cues to govern and sustain plant growth and survival. Although diverse sugar signals have emerged as pivotal regulators from embryogenesis to senescence, glucose is the most ancient and conserved regulatory signal that controls gene and protein expression, cell-cycle progression, central and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
195
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(206 citation statements)
references
References 148 publications
(384 reference statements)
4
195
0
7
Order By: Relevance
“…The glucosinolate content varies depending on genetic and environmental factors, and is modulated by external signals such as sugar (Miao et al, 2013) and phytohormones (Yuan et al, 2009;Sun et al, 2012;Wang et al, 2012;Guo et al, 2013a;2013b;Huseby et al, 2013;Kim et al, 2013;Zang et al, 2015). Glucose is not only the basal carbon and energy source but also a signaling molecule having regulatory effects throughout the life cycle of plant (Sheen, 2014). Our previous studies showed that glucose dramatically increases glucosinolate content in both Arabidopsis and crop brassicas (Wei et al, 2011;Guo et al, 2013c;Miao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The glucosinolate content varies depending on genetic and environmental factors, and is modulated by external signals such as sugar (Miao et al, 2013) and phytohormones (Yuan et al, 2009;Sun et al, 2012;Wang et al, 2012;Guo et al, 2013a;2013b;Huseby et al, 2013;Kim et al, 2013;Zang et al, 2015). Glucose is not only the basal carbon and energy source but also a signaling molecule having regulatory effects throughout the life cycle of plant (Sheen, 2014). Our previous studies showed that glucose dramatically increases glucosinolate content in both Arabidopsis and crop brassicas (Wei et al, 2011;Guo et al, 2013c;Miao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies on the enzymatic functionality of glycolysis have determined the importance of phosphoglucomutase (PGM) in starch formation processes in both heterotrophic (root and seed) and autotrophic tissues as well as the role of hexokinases (HXK) and other enzymes such as the glucose signaling network (Sheen, 2014). Regarding the TCA cycle, some progress has been made in understanding how alternative pathways involving γ-aminobutyric acid (GABA) and the glyoxylate cycle operate, with special attention given to changes in the optimal conditions, in order to show the high level of plasticity in the response of the TCA cycle to environmental changes (Sweetlove et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Glucose (Glc) and sucrose (Suc), 2 kinds of metabolic sugars that are widely present in plants, have been recognized as pivotal integrating regulatory molecules that control gene expression related to plant metabolism, stress responses, and other growth and development related processes including seed germination, floral transition, fruit ripening, embryogenesis, and senescence. [2][3][4] While little is known to the signaling mechanisms of Suc, part of the signal transduction pathways of Glc in plants has been established, which include 3 distinct pathways: HEXOKINASE1 (HXK1)-dependent pathway, HXK1-independent pathway, and glycolysis-dependent pathway that utilizes the SUCROSE NONFERMENTING RELATED KINASE1 (SnRK1)/TARGET OF RAPAMYCIN (TOR) pathway. 5 Discovery of unique and global repression of photosynthetic genes by Glc in Arabidopsis led to identification of HXK1 as the first plant Glc sensor, which mediates Glc repression or promotion of gene transcription and plant growth.…”
mentioning
confidence: 99%
“…6,7 Later on, diverse isoforms of HXK and HXK-like (HXL) genes were found in the genomes of many plants, including rice, maize, tomato, tobacco and Arabidopsis, which suggests that plants have evolved a complex mode of Glc signaling to support various growth strategies and architectures dictated by sugar availability. 4,7 Suc is the major transport sugar in higher plants and could also initiate signaling pathways leading to changes of gene expression and physiological adaptation, but a Suc sensor has not be identified. 8 Brassinosteroids (BRs) are a class of polyhydroxylated sterol derivatives that regulate diverse developmental and physiological processes, including seed germination, seedling photomorphogenesis, stomata differentiation, organ boundary formation, flowering, male fertility, and even responses to biotic and abiotic stresses.…”
mentioning
confidence: 99%
See 1 more Smart Citation